Identification of Quality of Life for Patients with Type II Diabetes Mellitus - Mohanad Jasim Salah; Ghazwan Abdulhussein Al-Abedi (Journal of Biomedicine and Biochemistry, 2024)
Background Type 2 diabetes, an adult chronic illness, impacts most body processes. Drug therapy assists in alleviating disease symptoms, but self-care is most important. Learning about the weak features of these behaviors and their relationship to the patient’s demographic factors can help nurses plan suitable nursing interventions to rectify and strengthen these behaviors and change the poor ones. Objective This study examines type II diabetes patients’ quality of life and whether demographic and socioeconomic data affect it.Methods The present study employed a descriptive design at Al- Diwaniya Teaching Hospital at the Diabetes and Endocrine Centre. This governmental hospital is Al-Diwaniya City’s largest general hospital. The sample was taken five months prior. 150 type 2 diabetic center patients were selected as a non-probability convenience sample. The questionnaire sheet includes sociodemographic factors and quality of life. Eleven special- ists examined the tool and utilized Cronbach’s alpha to check its content validity in the pilot study to ensure its reliability. Results TType II Diabetes Mellitus patients’ quality of life was as- sessed. 90% of consumers perceive a moderate quality of life (M±SD= 81.12 ± 10.529). A significant relationship exists between patients’ quality of life and their sex, level of education, occupation, and monthly income (p-values=0.013,0.001,0.001, and 0.031), but not with their age, marital status, or residency. Conclusion The study evaluated the quality of life for type II Diabetes Mellitus patients and found that most had moderate quality of life. Sex, ed- ucation, occupation, and monthly income were significantly associated with quality of life at p-values=0.013,0.001,0.001, and 0.0031. Non-significant with another variable.